Higher Order Thinking-Based Fiqh Evaluation Instrument for Senior High School for the Analysis of Students’ Complex Cognitive Abilities in Islamic Religious Education - Lestari, Dwi; Risnita, Risnita; Sastradika, Dedi; Ramdayeni Sakunti, Sri (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2026)
The main objective of this study is to develop an HOTS instrument in the Islamic Religious Education subject, fiqh material, in the form of 40 multiple-choice questions. This study is a Research and Development (R&D) study using the 4D model, limited to the Development stage. The experimental subjects in this study were 313 12th-grade high school students in Jambi City. Data were collected through expert validation and instrument trials. Data analysis was carried out using Aiken's V index and the Rasch model item response theory using QUEST software. The Aiken's V results reached 0.95, which is classified as very valid. Meanwhile, the results of the Rasch model analysis showed an item reliability value of 0.96 and a person reliability value of 0.90. 75% of the questions developed were included in the medium difficulty category, and there were 36 items that were declared appropriate and 4 items that were declared inappropriate. Based on these results, it can be concluded that the HOTS instrument for fiqh material meets the criteria of being valid, reliable, and suitable for use, although there are still several items that need to be revised.